1998
DOI: 10.1074/jbc.273.36.23046
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Activates the Human Histidine Decarboxylase Promoter in AGS Gastric Cancer Cells

Abstract: Oxidant stress is thought to play a role in the pathogenesis of many gastric disorders. We have recently reported that histidine decarboxylase (HDC) promoter activity is stimulated by gastrin through a protein kinase C-and extracellular signal-regulating kinase (ERK)-dependent pathway in gastric cancer (AGS-B) cells, and this transcriptional response is mediated by a downstream cis-acting element, the gastrin response element (GAS-RE). To study the mechanism through which oxidant stress affects gastric cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
47
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 44 publications
2
47
0
Order By: Relevance
“…8C). Additionally, application of an inhibitory Ras mutant (N15) substantially impaired the effect of H 2 O 2 on the VEGF-A promoter, confirming our previous observation that oxidative stress activates the Raf-1/MEK1/ERK1/2 kinase cascade in gastric cancer cells through (a) Ras-dependent mechanism(s) (37). These findings are compatible with the concept of the Raf/MEK1/ERK1/2 cascade being a critical signaling in VEGF-A gene regulation as shown in other experimental systems including acidic pH challenge of human glioma cells (51), insulin-like growth factor-I stimulation of NIH3T3 fibroblasts (52), and hamster fibroblast models (30).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…8C). Additionally, application of an inhibitory Ras mutant (N15) substantially impaired the effect of H 2 O 2 on the VEGF-A promoter, confirming our previous observation that oxidative stress activates the Raf-1/MEK1/ERK1/2 kinase cascade in gastric cancer cells through (a) Ras-dependent mechanism(s) (37). These findings are compatible with the concept of the Raf/MEK1/ERK1/2 cascade being a critical signaling in VEGF-A gene regulation as shown in other experimental systems including acidic pH challenge of human glioma cells (51), insulin-like growth factor-I stimulation of NIH3T3 fibroblasts (52), and hamster fibroblast models (30).…”
Section: Discussionsupporting
confidence: 72%
“…In gastric cancer cells, Ras-dependent activation of the Raf 3 MEK1 3 ERK1/2 kinase module has been shown to be a major pathway through which oxidative stress can influence transcriptional responses (37). Our current study shows that H 2 O 2 treatment of gastric cancer cells at a concentration of 1 mM led to increased phosphorylation of ERK1/2, MEK1, p38, and JNK, indicating activation of associated upstream kinases (Fig.…”
Section: Discussionmentioning
confidence: 58%
“…In addition to its central role in regulation of gastric acid secretion, increased HDC gene expression has also been found to be associated with gastric inflammation and development of gastroduodenal ulceration (31)(32)(33)(34)(35). Furthermore, we found that oxidative stress, which is commonly increased in ulcerative and inflammatory diseases affecting the gastric mucosa, is capable of transactivating the hHDC promoter in vitro (36). Aside from its ulcerogenic potential, histamine has also been shown to possess immunomodulatory properties in the context of mucosal inflammations, contributes to the healing of ulcerative lesions of the gastric and intestinal mucosa, and has also been shown to stimulate the growth of gastric epithelial cells (37)(38)(39)(40)(41).…”
mentioning
confidence: 64%
“…Although some overlap between both pathways has been described (46), the JNK cascade activates primarily transcription factors involved in the "stress response" of eukaryotic cells, whereas the ERK pathway has been linked to genes involved in cellular proliferation and differentiation (46 -48). Recently we demonstrated that ERK-related signaling cascades also play a central role in the transmission of the effects of gastrin and oxidative stress on the hHDC promoter in gastric cancer cells, whereas the JNK pathway is not involved in hHDC gene regulation (36,49). Therefore, it is highly likely that the ERK cascade represents a potential target signaling route through which activators of hHDC gene transcription exert their transactivating effect on the hHDC promoter.…”
mentioning
confidence: 99%
“…HDC promoter activity is up-regulated by several different stimuli, including gastrin (8), phorbol ester phorbol 12-myristate 13-acetate (8 -11), oxidative stress (12), thrombopointin (13), and Helicobacter pylori infection (14,15). Whereas not all of the cis-acting DNA elements or the transcriptional factors involved in regulation of HDC transcription have been identified, three GC-rich gastrin responsive elements located downstream of the transcription initiation site have been characterized in the human HDC promoter region (16,17).…”
mentioning
confidence: 99%